Compact wideband and high gain horn slot antenna array fed by printed ridge gap waveguide for X band applications - Mahboubeh Taraji; Elham Baladi; Marco A. Antoniades (Scientific Reports)
Abstract The design and implementation of a wideband low-loss H-plane horn slot antenna array excited by a 2-by-2 bottom-fed planar corporate feeding network is presented in this paper. The feeding network is presented by a 2-by-2 symmetric power dividing system designed to feed a 2-by-2 slot antenna array from bottom. The feeding network is realized using printed ridge gap waveguide technology as a magnetic ground, to suppress surface wave propagation and to enable quasi-TEM wave propagation along the microstrip feed. Each of the power-divider branches in the feeding network excites a slot, while maintaining the impedance bandwidth of the original unloaded power divider. The feeding mechanism and H-plane horn elements help to control the sidelobe levels and increase the overall gain. The measured results are in good agreement with the simulations, with an impedance bandwidth of over 58.5%, covering the entire X-band, with a peak gain of 14.1 dBi at 10 GHz, and a measured radiation efficiency greater than 86% throughout the operating frequency range, with a peak of 99% at 10 GHz. These are significant improvements compared to an impedance bandwidth of less than 25% and a gain of 11 dBi for the antenna array without the horn elements. The antenna has a compact size of $$4.8× 4.8× 1.5\,\text {cm}^{2}$$ or 1.6 $$λ _0×$$ 1.6 $$λ _0×$$ 0.5 $$λ _0$$ at 10 GHz.